An Efficient Resource Management Protocol for Handling Small Resource in Wireless Sensor Networks - Wan-Hee Cho; Jiho Kim; Ohyoung Song (International Journal of Distributed Sensor Networks)
Wireless sensor nodes with single chips may have insufficient resources for certain applications. We propose a resource management protocol for applications with constrained resources to improve effectiveness by borrowing resources from a resource management server.